Molecular Interactions Between Innate and Adaptive Immune Cells in Chronic Lymphocytic Leukemia and Their Therapeutic Implications - Haseeb, Muhammad; Anwar, Muhammad Ayaz; Choi, Sangdun (Frontiers in Immunology, 2018)
Innate immunity constitutes the first line of host defense against various anomalies in humans, and it also guides the adaptive immune response. The function of innate immune components and adaptive immune components are interlinked in hematological malignancies including chronic lymphocytic leukemia (CLL), and molecular interactions between innate and adaptive immune components are crucial for the development, progression and the therapeutic outcome of CLL. In this leukemia, genetic mutations in B cells and B cell receptors (BCR) are key driving factors along with evasion of cytotoxic T lymphocytes and promotion of regulatory T cells. Similarly, the release of various cytokines from CLL cells triggers the protumor phenotype in macrophages that further edges the CLL cells. Moreover, under the influence of various cytokines, dendritic cells are unable to mature and trigger T cell mediated antitumor response. The phenotypes of these cells are ultimately controlled by respective signaling pathways, the most notables are BCR, Wnt, Notch, and NF-κB, and their activation affects the cytokine profile that controls the pathogenesis of CLL, and challenge its treatment. There are several novel substances for CLL under clinical development, including kinase inhibitors, antibodies, and immune-modulators that offer new hopes. DC-based vaccines and CAR T cell therapy are promising tools; however, further studies are required to precisely dissect the molecular interactions among various molecular entities. In this review, we systematically discuss the involvement, common targets and therapeutic interventions of various cells for the better understanding and therapy of CLL.